ORNITHONYMS IN ROOT WORD POSITION (Scientific journal of the Fergana State University, 2024)
This article is devoted to the issues of ornithonyms in the position of root words, and it was observed that such words are relatively rare in the languages being mixed. From the point of view of the modern language, all ornithonymous lexemes that cannot be derived from a specific word formation pattern are root words and are used as ready-made lexemes in speech.